Lens Capsular Glutathione Level and Glutathione Peroxidase Activity Among Diabetic Patients (Annals of Medical Research, 2021)
None
Keywords: Cataract, Diabetes mellitus, Glutathione (GSH), Glutathione peroxidase (GSH-Px), Meticulous controlled diabetes